Strategies for the reduction of Campylobacter thermotolerants in broilers (Research, Society and Development, 2020)
Thermotolerant Campylobacter is related to a group of foodborne pathogens that are currently considered to be the main causes of globally occurring gastrointestinal diseases with high frequency of antimicrobial resistance. Therefore, this review aims to discuss alternatives for the control and reduction of microorganism in broiler, like biosecurity actions and nutritional strategies. Thus, it is possible to list feasible measures relating to the overall management plan for chickens from housing to transport to slaughterhouses, as well as biological and / or chemical components associated with the broiler’s feed so that they minimize contamination and, as a result, the spread of the bacteria during slaughter operations, the transmission of pathogens by food and the risk to public health.